Instability of nonminimally coupled scalar fields in the spacetime of slowly rotating compact objects - Mendes, Raissa F. P. [UNESP]; Matsas, George E. A. [UNESP]; Vanzella, Daniel A. T. (Amer Physical Soc, 2014)
Nonminimally coupled free scalar fields may be unstable in the spacetime of compact objects. Such instability can be triggered by classical seeds or, more simply, by quantum fluctuations giving rise to the so-called "vacuum awakening effect." Here, we investigate how the parameter space that characterizes the instability is affected when the object gains some rotation. For this purpose, we focus on the stability analysis of nonminimally coupled scalar fields in the spacetime of slowly spinning matter shells.